2020
DOI: 10.1021/acs.inorgchem.0c01339
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hydrogen Evolution Reaction Activities of 2H-Phase VS2 Layers with Palladium Nanoparticles

Abstract: Effective hydrogen (H2) production with surface engineering of less active catalysts by an innovative approach is followed here. In this work, a non-noble 2H phase of VS2 layers, which showed poor activity for hydrogen evolution reaction (HER) in 0.5 M H2SO4, was made highly active by decorating palladium (Pd) nanoparticles (NPs) over VS2 layers. A density functional theory (DFT) study confirmed the successful binding of Pd with VS2, and the bond length in a Pd4 tetrahedron was measured to be 2.60 Å. In VS2–Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…In addition, long‐term stability at 10 mA cm −2 was also measured for the V 1.11 S 2 , 0.5Mo–V 1.11 S 2 , and 0.5Mo–V 1.11 S 2‐x electrocatalyst‐based electrode. As shown in Figures 3e and S8, during the 24 h operation, the potential of 0.5Mo–V 1.11 S 2‐x remained extremely stable at a current density of 10 mA cm −2 , better than V 1.11 S 2 , 0.5Mo–V 1.11 S 2 and many recently reported vanadium‐based HER electrocatalysts [58–59,64] . For comparison, the potential of 20 wt.% Pt/C drops dramatically with the extension of test time, which is consistent with previous studies [65–66] .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, long‐term stability at 10 mA cm −2 was also measured for the V 1.11 S 2 , 0.5Mo–V 1.11 S 2 , and 0.5Mo–V 1.11 S 2‐x electrocatalyst‐based electrode. As shown in Figures 3e and S8, during the 24 h operation, the potential of 0.5Mo–V 1.11 S 2‐x remained extremely stable at a current density of 10 mA cm −2 , better than V 1.11 S 2 , 0.5Mo–V 1.11 S 2 and many recently reported vanadium‐based HER electrocatalysts [58–59,64] . For comparison, the potential of 20 wt.% Pt/C drops dramatically with the extension of test time, which is consistent with previous studies [65–66] .…”
Section: Resultssupporting
confidence: 88%
“…As shown in Figures 3e and S8, during the 24 h operation, the potential of 0.5Mo-V 1.11 S 2-x remained extremely stable at a current density of 10 mA cm À 2 , better than V 1.11 S 2 , 0.5Mo-V 1.11 S 2 and many recently reported vanadium-based HER electrocatalysts. [58][59]64] For comparison, the potential of 20 wt.% Pt/C drops dramatically with the extension of test time, which is consistent with previous studies. [65][66] Moreover, the polarization curve of À 2 , (e) the stable operation of the 0.5Mo-V 1.11 S 2-x electrode running at the current density of 10 mA cm À 2 , and 100 mA cm À 2 in 0.5 mol L À 1 H 2 SO 4 for a total duration of 24 h. ChemistrySelect 0.5Mo-V 1.11 S 2-x after 24 h operation remains nearly unchangeable (Figure S9).…”
Section: Chemistryselectsupporting
confidence: 91%
“…[8][9][10][11] However,t heir large-scale industrial applicationsh ave been limited due to high cost and poor stability. [12,13] Therefore, cost-effective and highly efficient tran-sition metal compounds such as transition metal oxides, [14,15] carbides/nitrides, [16][17][18] sulfides, [19][20][21] and phosphides [22][23][24][25] have attracted ag reat deal of attention for HER.…”
Section: Introductionmentioning
confidence: 99%
“…These results have demonstrated that the screening principles can be easily implemented in computer programs for the high-throughput screening of NMs with intrinsic SOD-like activity. Among these materials, T-phase transition metal dichalcogenides (T-TMDCs, PtS 2 45 , ZrS 2 46 , ZrSe 2 46 , SnS 2 47 , HfS 2 48 ) and H-TMDCs (MoTe 2 49 , WSe 2 50 , WTe 2 51 , VS 2 52 ) have been experimentally reported. They existed in the form of single layers supported on substrates or a few layers in solutions 53 – 57 .…”
Section: Resultsmentioning
confidence: 99%